Kasabach-Merritt Syndrome in Liver Hemangioma: A Case Report - Frastica, Michelle; Putranto, Rudi; Jasirwan, Chyntia Olivia Maurine; Adhiatma, Kresna (UI Scholars Hub, 2022)
Hemangioma is the most common congenital benign liver tumor. It affects mostly female, with the incidence of 0.4- 20%. Giant liver hemangioma induce the Kasabach Merritt syndome, a life threathening coagulation disorder which occur due to consumptive coagulopathy: trombocyte sequestration and agregation inside the hemangioma. The mortality rate is around 60%, with the most common cause is multiorgan complication which may end up with sepsis. The core management is hemangioma decompression by surgical measure. However, this often considered as a very risky procedure leading to massive bleeding. In most cases, conservative treatment is the preferred option. It is important to consider Kasabach Merritt syndome as one of the differential diagnosis when facing cases with enlarged abdomen in order to plan for its treatment as well as educate the patients regarding the prognosis.